1986
DOI: 10.1073/pnas.83.2.474
|View full text |Cite
|
Sign up to set email alerts
|

Bismuth-212-labeled anti-Tac monoclonal antibody: alpha-particle-emitting radionuclides as modalities for radioimmunotherapy.

Abstract: Anti-Tac, a monoclonal antibody directed to the human interleukin 2 (IL-2) receptor, has been successfully conjugated to the a-particle-emitting radionuclide bismuth-212 by use of a bifunctional ligand, the isobutylcarboxycwrbonic anhydride of diethylenetriaminepentaacetic acid. The physical properties of 212Bi are appropriate for radioimmunotherapy in that it has a short half-life, deposits Its high energy over a short distance, and can be obtained in large quantities from a radium generator. Antibody specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
41
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 160 publications
(41 citation statements)
references
References 17 publications
0
41
0
Order By: Relevance
“…Although therapeutic effects have been achieved with compartmentally delivered non-specific 2"'At preparations in murine models (Bloomer et al, 1984;Vergote et al, 1992), the use of 2"'At-labelled compounds with some degree of selective tumour uptake seems to be the most promising strategy (Humm, 1987;Humm & Chin, 1993). The therapeutic potential of a-emitters is increased when they are coupled to molecules with high tumour affinity because of the short range and high ionisation density of a-particles (Brown, 1986;Kozak et al, 1986;Kurtzman et al, 1988;Macklis et al, 1989).We have recently studied the cytotoxicity of 2"At-TP-3 monoclonal antibody (MAb) on single-cell suspensions of three human osteosarcoma cell lines (OHS, SAOS and KPDX) (Larsen et al, 1994). The study showed that the sensitivity to 2"1At-TP-3 treatment was governed by cellular properties other than those governing sensitivity to treatment with external beam X-rays.…”
mentioning
confidence: 99%
“…Although therapeutic effects have been achieved with compartmentally delivered non-specific 2"'At preparations in murine models (Bloomer et al, 1984;Vergote et al, 1992), the use of 2"'At-labelled compounds with some degree of selective tumour uptake seems to be the most promising strategy (Humm, 1987;Humm & Chin, 1993). The therapeutic potential of a-emitters is increased when they are coupled to molecules with high tumour affinity because of the short range and high ionisation density of a-particles (Brown, 1986;Kozak et al, 1986;Kurtzman et al, 1988;Macklis et al, 1989).We have recently studied the cytotoxicity of 2"At-TP-3 monoclonal antibody (MAb) on single-cell suspensions of three human osteosarcoma cell lines (OHS, SAOS and KPDX) (Larsen et al, 1994). The study showed that the sensitivity to 2"1At-TP-3 treatment was governed by cellular properties other than those governing sensitivity to treatment with external beam X-rays.…”
mentioning
confidence: 99%
“…Sizeable fluctuations (at least by a factor of 4) in the local dose have been shown by implanting micro-thermoluminescent dosimeters in tumours (Griffith et al, 1988). In vitro survival curves with 212 Bi-labelled membrane specific and non-specific antibodies have demonstrated marked high efficiencies in cell killing due to antibody binding (Kozak et al, 1986). Calculations of the energy deposited in the cell nuclei resulting from antibody binding have shown significant departures from the mean energy deposition resulting from a uniform distribution of the label, an implicit assumption of the conventional MIRD procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Calculations of dose to tumour based on the assumption of a uniform distribution therein may well underestimate the cytotoxicity to individual cells within the mass. It has been suggested that radiolabelled antibodies to membrane-bound antigens on cells in vitro have a greater potential for cell kill (Kozak et al, 1986), while released antigen may adversely affect antibody localisation in xenografts (Pedley et al, 1989). A comparative study of the distribution and retention of 17-1-A (Herlyn et al, 1983(Herlyn et al, , 1986) and anti-carcinoembryonic antigen 11-285-14 antibodies (Lewis et al, 1984) over time by autoradiography in two distinct human colorectal cancer xenografts MAWI and TAF (Lewis et al, 1983) serves to demonstrate how the inherent temporal and spatial heterogeneity of isotope localisation in the tumours might be exploited.…”
mentioning
confidence: 99%
“…The x-particle emitting radionuclides fall into this class and a number of research groups are pressing the case for the use of a emitters in RIT (Vaughan et al, 1982;Harrison & Royle, 1984;Kozak et al, 1986). Harrison and Royle (1986) have shown that astatine-211 labelled McAb can cure early T cell lymphoma in mice, and Kozak and his co-workers (1986) have reported that in vitro bismuth-212 labelled anti-Tac greatly reduces the proliferative capacity of a human T cell lymphoma line.…”
Section: Radionuclidesmentioning
confidence: 99%